Promosi Taman Nasional Takabonerate Kabupaten Kepulauan Selayar Melalui Media Sosial - Nur Afiah (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to analyze the promotional strategy for Takabonerate National Park through social media. Promotions are used through social media created by the National Park Office and the Selayar Tourism Service such as YouTube, Instagram, Twitter, tiktok, website and Facebook so that visitors or tourists, both domestic and international, visit more and find out information related to TNTB in detail and accurately. This research use a qualitative descriptive method. By conducting interviews and observations, and data from references study, journal, magazine, and online media based in the analysis involved. The results of this research are to find out whether the use of promotion via social media has a more positive impact and is most appropriate for use by the Takabonerate National Park Center and the Selayar Tourism Service because the cost of promotion via social media is relatively cheap and efficient given the TNTB location.